2020
DOI: 10.3390/pathogens9110960
|View full text |Cite|
|
Sign up to set email alerts
|

Altered Salivary Microbiome in the Early Stage of HIV Infections among Young Chinese Men Who Have Sex with Men (MSM)

Abstract: Human immunodeficiency virus (HIV) infections are spiking in Chinese young men who have sex with men (MSM). To explore alterations in the salivary microbiome and its correlation with demographic characteristics, CD4+ T cell count and viral load (VL) in HIV infections, samples of unstimulated whole saliva were analyzed by 16S rRNA gene sequencing using the Illumina MiSeq platform in 20 HIV newly infected patients before the initiation of antiretroviral therapy (ART) and at three and six months after, and in 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Additionally, salivary components, such as salivary IgA, lactoferrin, defensins, and epithelial cell-mediated cytokines, are altered in PLWH, resulting in the occurrence of frequent oral infections (Muller et al, 1992). A recent study reported that the changes of salivary microbiome in HIV infection and found that Streptococcus was enriched in HIV-infected individuals, whereas the richness of Neisseria was high in healthy controls (Li et al, 2020). In present study, we observed that the abundance of unidentified Prevotellaceae in both groups of patients with acute and chronic HIV infection was increased as well as the abundances of Prevotella in acute HIV individuals and Streptococcus in chronic HIV individuals.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Additionally, salivary components, such as salivary IgA, lactoferrin, defensins, and epithelial cell-mediated cytokines, are altered in PLWH, resulting in the occurrence of frequent oral infections (Muller et al, 1992). A recent study reported that the changes of salivary microbiome in HIV infection and found that Streptococcus was enriched in HIV-infected individuals, whereas the richness of Neisseria was high in healthy controls (Li et al, 2020). In present study, we observed that the abundance of unidentified Prevotellaceae in both groups of patients with acute and chronic HIV infection was increased as well as the abundances of Prevotella in acute HIV individuals and Streptococcus in chronic HIV individuals.…”
Section: Discussionsupporting
confidence: 65%
“…A previous study reported that Haemophilus parainfluenzae was significantly associated with HIV-positive individuals, and it was positively correlated with CD4 + T cell counts within the HIV-positive group (Kistler et al, 2015). However, a recent study found that the genus Haemophilus was correlated negatively with CD4 + T cell count (Li et al, 2020). The possible reasons for the different results might include the different study subjects, samples, the small sample sizes, and other possible factors not involved in the analysis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Since all of our study subjects for the oral microbiome-related studies were on ART, we were unable to investigate the potential effects of ART on the oral microbiome. However, it was reported that the dysbiotic oral microbiome was not fully restored after effective ART, although some microbiota were restored ( 51 ). Furthermore, ART, viral load, and CD4 + T cell count differentially contribute to salivary dysbiosis resulting in reduced or increased different bacterial species ( 27 ).…”
Section: Discussionmentioning
confidence: 99%